2018
DOI: 10.1002/ps.5163
|View full text |Cite
|
Sign up to set email alerts
|

Carfentrazone‐ethyl and glyphosate drift inhibits uredinial formation of Austropuccinia psidii on Eucalyptus grandis leaves

Abstract: Glyphosate and carfentrazone-ethyl herbicide drift reduce infection and uredinial formation of A. psidii and to some extent induce basal resistance in a susceptible clone of E. grandis. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…Durante operações convencionais de pulverização, há possibilidade de ocorrência de deriva da calda herbicida que pode atingir e afetar o desenvolvimento de plantas não alvo. Nesse caso, o contato direto do glyphosate em plantas de eucalipto pode promover sintomas de intoxicação e alteração no crescimento das plantas (SANTOS JÚNIOR et al, 2015;SALGADO et al, 2017;SANTOS et al, 2019). Na aplicação localizada de herbicidas em inserção direta no fuste das árvores de eucalipto antes do corte raso, a ocorrência de deriva e o contato direto do herbicida com organismos não alvo, solo ou corpos hídricos é praticamente nula.…”
Section: Resultsunclassified
“…Durante operações convencionais de pulverização, há possibilidade de ocorrência de deriva da calda herbicida que pode atingir e afetar o desenvolvimento de plantas não alvo. Nesse caso, o contato direto do glyphosate em plantas de eucalipto pode promover sintomas de intoxicação e alteração no crescimento das plantas (SANTOS JÚNIOR et al, 2015;SALGADO et al, 2017;SANTOS et al, 2019). Na aplicação localizada de herbicidas em inserção direta no fuste das árvores de eucalipto antes do corte raso, a ocorrência de deriva e o contato direto do herbicida com organismos não alvo, solo ou corpos hídricos é praticamente nula.…”
Section: Resultsunclassified
“…Commercially formulated glyphosate was recently shown to be as effective as a commercial fungicide in suppressing rice blast ( Magnaporthe oryzae ) in GR rice, and the authors indicated that the effect was solely through the fungicidal effects of glyphosate . Low doses of glyphosate even reduced infection of glyphosate-sensitive eucalyptus by Austropuccinia psidii . Several field studies have reported no effect of glyphosate used for weed management in GR crops on crop diseases .…”
Section: Target Sites Of Commercial Herbicides Found In Fungi That Ar...mentioning
confidence: 99%